Analysis of anthocyanin colour stability from fruits pulp of melastoma malabathricum / Norkasmani binti Aziz - Aziz, Norkasmani (2012)
The aim of this dissertation is to evaluate suitability of anthocyanin from M. malabathricum as potential natural colourant for coating system and also to evaluate the colour stability of anthocyanin colorant with and without Ferulic acid (FA) stabilising agent in a polyvinyl alcohol (PVA) binder coating system. Besides that the purpose for this project is to analyse the colour stability of potential natural colourant in a coating system in terms of percentage of FA and pH toward UV-B irradiation using CIE system. The anthocyanin colourant from M.malabathricum using acidified methanol for crude and purified colourant. Purification was performed by liquid-liquid partition and ion exchange column chromatography. Different percentages of Ferulic acid as stabilising agent in order to improve resistance towards UV-B irradiation during the exposure period. FA added colourant was mixed with PVA to develop a coating system. To test colour stability of crude and purified anthocyanin colorant and anthocyanin-PVA blend towards UV-B irradiation,CIE colour analysis was carried out. CIE results were analysed in terms of L*C*H*a* and b* co-ordinate.Colour differences ΔE and saturation of colour, (s) were calculated in order to evaluate the visual colour variation in this study. CIE results shows that the colour variation of anthocyanin and anthocyanin-PVA blend both crude and purified affected by the addition of FA. The addition of 3% FA at pH3 showed better stability.